Effects of TiO2 electrode thickness on the performance of dye solar cell by simulation - Oktiawati, U.Y. (2013)
Dye solar cells (DSC) are technically attractive in providing a renewable, cost efficient energy source with low environmental impact. DSC are based on photo electrochemical cells (PEC) which consist of mesoporous TiO2 semiconductor film coated with photo sensitizing dyes and a charge transport layer of a liquid electrolyte. Although the quantum efficiency of DSCs is efficient, but the effect of each component on its overall efficiency is yet to be understood in order to achieve an optimized cell. One of the critical components of DSC is TiO2 electrode thickness. This paper presents the effects of TiO 2 electrode thickness on the simulated performance of dye solar cell using Silvaco. It was found that the highest efficiency can be achieved with TiO2 electrode thickness of 10 Î¼m. Â© 2013 IEEE.